Percepção e atitude de homens e mulheres frente a mulher contemporânea: uma abordagem Junguiana - Almeida, Nilma Figueiredo de (1991)
This work has for aim, investigate the perception and attitude of men and women related to the contemporary woman. For this, it was achieve a field research, with five liable of the masculine sex and five liable of the feminine sex, with the variant of age between 25 to 41 years old. AlI belonging to the middle social class of Rio de Janeiro. All graduated. The theorical focus given at this research were based at the Analitic Psychology of C.G. Jung. Thru-this study, was done the verification that, in spite of the reconnaissance of the laboratorial capacity of the women and of also being occupying a space each time bigger as much in political life as in cientificaI of world, look like as it they were loosing sense of them in affective and home life terms. This criated a situation rather complicated to the interrelations plan owing to the difficulty of apprehension of both roles, masculine and feminine, from modern society.